Safe and Fault Tolerant Control of Industrial differential Drive Vehicles - Vito Racanelli; Saverio Mascolo (12th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes, 2024)
differential drive vehicles are an integral of industrial operations, where precise control is essential for safety and efficiency. These vehicles often employ encoders for precise maneuvering through closed-loop control. In this scenario, system failures can result in uncontrolled movements, posing significant risks to human operators. To address this issue, this paper proposes a robust and fail-safe controller model that ensures vehicle safety, even in the face of multiple failure scenarios. The proposed model provides a comprehensive solution to address various potential problems encountered in industrial environments. Based on fault tolerance and control theory principles, our model incorporates innovative strategies to mitigate encoder failures, sensor malfunctions, and other related system faults. The design and performance of the controller are thoroughly analyzed to demonstrate its effectiveness in preventing catastrophic failures in industrial environments.
12th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes SAFEPROCESS 2024